Inactivation of Salmonella spp. and Listeria spp. by Palmitic, Stearic, and Oleic Acid Sophorolipids and Thiamine Dilauryl Sulfate - Zhang, Xuejie; Ashby, Richard; Solaiman, Daniel K. Y.; Uknalis, Joseph; Fan, Xuetong (Frontiers in Microbiology, 2016)
Food contaminated with human pathogens, such as Salmonella spp. and Listeria monocytogenes, frequently causes outbreaks of foodborne illness. Consumer concern over the use of synthesized antimicrobials to enhance microbial food safety has led to a search of natural alternatives. The objectives of this study were to evaluate the antimicrobial activity of various types of sophorolipids (SLs) and thiamine dilauryl sulfate (TDS) against pathogenic Salmonella spp. and Listeria spp. Both free and lactonic forms of SLs were synthesized from Candida bombicola using palmitic, stearic and oleic acids as co-feedstocks. TDS and purified SLs were used to treat cocktails of Salmonella spp. and Listeria spp. Results showed that lactonic SLs had higher antimicrobial activity than the free-acid form, and Gram-positive Listeria spp. were more susceptible to SLs and TDS than Gram-negative Salmonella spp. Listeria populations were reduced from an initial concentration of 7.2 log CFU/mL to a non-detectible level within a 1 min treatment of 0.1% (w/v) lactonic SLs and TDS in the presence of 20% ethanol, which itself did not significantly reduce the populations. There were no significant differences in the antimicrobial efficacy among palmitic, stearic and oleic acid-based SLs against Salmonella or Listeria spp. Ethanol was utilized to improve the antimicrobial activity of free-acid SLs against Gram-negative bacteria. In general, TDS was more effective than the SLs against Salmonella and Listeria spp. SEM and TEM images showed that SLs and TDS damaged Listeria cell membranes and resulted in cell lysis. Overall, our results demonstrated that SLs and TDS in the presence of ethanol can be used to inactivate foodborne pathogens, especially Gram-positive bacteria.